Branch structure nanofiber air filtering material as well as preparation method and application thereof

By modifying polyvinylidene fluoride hexafluoropropylene in two-dimensional transition metal titanium carbide and dopamine hydrochloride to regulate spinning hydraulic conductivity, branch structure nanofiber air filter material was prepared, and the pore size of existing air filter material was solved. The problems of large, large resistance, low efficiency and other problems have achieved high efficiency and low resistance, reusable and good mechanical properties.

CN119455526APending Publication Date: 2025-02-18INST OF MEDICAL SUPPORT TECH OF ACAD OF SYST ENG OF ACAD OF MILITARY SCI
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411590941.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-08
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

Existing air filter materials have problems such as large pore size, large air resistance, low filtration efficiency, high cost, poor durability and environmental pollution, and it is difficult to meet the needs of high efficiency and low resistance, reusable and good mechanical properties.

Method used

The two-dimensional transition metal titanium carbide was used to modify polyvinylidene fluoride total hexafluoropropylene, and the conductivity of the spinning liquid was regulated by dopamine hydrochloride, and the branch structure nanofiber air filter material was prepared by electrospinning technology.

Benefits of technology

This material has good mechanical properties, hydrophobicity and reusable characteristics, and the filtration efficiency of ultra-fine particulate matter can reach more than 99.96%, which is suitable for air filtration and medical and health fields.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119455526A_ABST
    Figure CN119455526A_ABST
Patent Text Reader

Abstract

The invention discloses a branch structure nanofiber air filtering material as well as a preparation method and application thereof, and belongs to the technical field of air filtering materials and preparation thereof. The material mainly comprises polyvinylidene fluoride co-hexafluoropropylene, polyvinylidene fluoride, two-dimensional transition metal titanium carbide Ti3C2Tx, dopamine hydrochloride and the like, the raw material polyvinylidene fluoride co-hexafluoropropylene is modified by adopting the two-dimensional transition metal titanium carbide, and the dopamine hydrochloride is adopted to regulate and control the conductivity of a spinning solution. According to the branch structure nanofiber air filtering material, the mechanical performance of fibers and the stability of a spinning solution in an electric field are effectively improved, the branch structure nanofiber air filtering material has the advantages of being good in mechanical performance and hydrophobicity and capable of being repeatedly used, and the filtering efficiency of superfine particles such as PM0.3 can reach 99.96% or above; the method has great application potential in the fields of air filtration and medical treatment and public health.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of air filter materials and preparation thereof, and in particular to a branch structure nanofiber air filter material, a preparation method and application thereof. Background Art

[0002] In recent years, the rapid development of global industry has led to the deterioration of the global environment. Inhalable particles in the environment are prone to carry harmful substances, posing a huge threat to human health. Air filter materials refer to materials used to filter impurities and harmful substances in the air. These materials usually have a large surface area, a small internal pore size and a large number of pores, which can effectively block the passage of dust particles, thereby achieving a filtering effect. They are widely used in air purification, medical and health and other air treatment fields, and are essential to improving indoor air quality and maintaining people's health.

[0003] At present, air filter materials are mainly melt-blown non-woven fabrics. The electrospun air filter materials that have been developed and applied have coarse fiber diameters, large pore sizes, large air resistance, and low filtration efficiency. In addition, the cost of PTFE (polytetrafluoroethylene) filter materials is relatively high, and their applicability in certain specific environments (such as extremely high or low temperatures) needs to be further verified; the glass fiber filter material is brittle, not wear-resistant, and has poor folding resistance, which limits its application in special fields; the electret filter material consumes electricity to maintain the electrostatic field, and the high humidity environment will affect its filtration effect, and it is also necessary to regularly clean or replace the dust collecting plate; the activated carbon fiber filter material needs to be regenerated or replaced after adsorption saturation, and will be affected by environmental factors such as temperature and humidity; the HEPA (high-efficiency particulate air) material and particulate filter material have relatively large resistance, require a large air volume to maintain its filtration efficiency, and have a high replacement cost. Although some scientific research teams have developed spider web-like nanofiber air filter materials, the material is thin, has low filtration efficiency, and has poor mechanical properties, making it difficult to promote and use. In addition, current air filter materials are mainly disposable products, which have caused serious environmental pollution problems. Therefore, there is an urgent need to develop a hydrophobic, reusable, multifunctional air filtration material with high efficiency, low resistance and good mechanical properties. Summary of the invention

[0004] Based on the technical problem to be solved by the present invention, the present invention uses two-dimensional transition metal titanium carbide to modify the raw material polyvinylidene fluoride co-hexafluoropropylene, uses dopamine hydrochloride to regulate the conductivity of the spinning solution, and prepares the dendritic structure nanofiber air filter material by electrospinning. The material effectively improves the mechanical properties of the fiber and the instability of the spinning solution in the electric field, has good mechanical properties, hydrophobicity and reusability, and is resistant to ultrafine particles such as PM 0.3 The filtration efficiency can reach over 99.96%, and it has great application potential in the fields of air filtration and medical health.

[0005] One of the purposes of the present invention is to provide a dendrite structure nanofiber air filter material, the dendrite structure nanofiber air filter material comprises a frame module and a filter module; further, the frame module is Ti 3 C 2 T x Functionalized polyvinylidene fluoride co-hexafluoropropylene nanofiber membrane; further, the filtration module is Ti 3 C 2 T x Functionalized polyvinylidene fluoride-co-hexafluoropropylene nanowires.

[0006] Furthermore, the Ti 3 C 2 T x The functionalized polyvinylidene fluoride-co-hexafluoropropylene nanofiber membrane is a disorderly distributed nanofiber; further, the Ti 3 C 2 T x Functionalized polyvinylidene fluoride co-hexafluoropropylene nanowires are interconnected, showing a typical tree structure.

[0007] Furthermore, the diameter of the frame module fiber is about 100-200 nm; further, the diameter of the filter module nanowire is about 20-80 nm.

[0008] The second object of the present invention is to provide a method for preparing a dendritic nanofiber air filter material, comprising:

[0009] S1. Mixing lithium fluoride and hydrochloric acid, stirring magnetically, to obtain a hydrofluoric acid solution;

[0010] S2. Etching away the Al atomic layer of titanium carbide in the hydrofluoric acid solution to obtain a two-dimensional titanium carbide nanosheet layer Ti 3 C 2 T x ;

[0011] S3. The two-dimensional titanium carbide nanosheet Ti 3 C 2 T x , added to N, N-dimethylformamide solution, and ultrasonically vibrated to obtain a solution in which two-dimensional titanium carbide nanosheets are dispersed in N, N-dimethylformamide in uniform size;

[0012] S4. adding dopamine hydrochloride to the solution containing the two-dimensional titanium carbide nanosheet layer, and ultrasonically shaking to obtain a two-dimensional titanium carbide nanosheet layer solution having good electrical conductivity;

[0013] S5. adding PVDF-HFP to the two-dimensional titanium carbide nanosheet solution having good electrical conductivity, and magnetically stirring to obtain an electrospinning solution;

[0014] S6. Laying the substrate flat on a flat receiver of an electrospinning machine, injecting the electrospinning solution into a syringe, placing the syringe on the electrospinning machine, adjusting parameters for electrospinning, and controlling the spinning time to prepare nanofiber membranes of different thicknesses;

[0015] S7. Place the nanofiber membrane in a stainless steel sterilization tray, place the stainless steel sterilization tray in a vacuum drying oven and dry for a certain period of time to completely evaporate the solvent, thereby obtaining a dendritic structure nanofiber air filtration material.

[0016] Further, the concentration of hydrochloric acid is 6mol / L to 12mol / L; further, the concentration of hydrochloric acid is 9mol / L; further, the lithium fluoride accounts for 10% to 20% of the hydrochloric acid; further, the lithium fluoride accounts for 15.6% of the hydrochloric acid.

[0017] Furthermore, in S1, the stirring time is 10 min to 2 h.

[0018] Furthermore, in S1, the stirring time is 30 minutes.

[0019] Furthermore, the titanium aluminum carbide is Ti 3 AlC 2 MAX phase.

[0020] Furthermore, the two-dimensional titanium carbide nanosheet layer is Ti 3 C 2 T x ; Wherein, x is a number, which is a natural number; T is a surface terminal group; the surface terminal group includes fluorine (-F), chlorine (-Cl), hydroxyl (-OH), oxygen (=O), etc.

[0021] Furthermore, the Ti 3 C 2 T x The mass ratio of the Ti to the N,N-dimethylformamide solvent is 1:300-1:700; further, the Ti 3 C 2 T x The mass ratio of the Ti to the N,N-dimethylformamide solvent is 3:1491; further, the Ti 3 C 2 T x The mass is 0.01g-0.05g, the volume of N,N-dimethylformamide is 10ml-24ml; further, the Ti 3C 2 T x The mass is 0.03g and the volume of N,N-dimethylformamide is 17ml.

[0022] Furthermore, in S3, the ultrasonic time is 10 min to 2 h; further, in S3, the ultrasonic time is 30 min.

[0023] Further, the amount of dopamine hydrochloride added is 0.01g to 0.1g; further, the amount of dopamine hydrochloride added is 0.05g; further, in S4, the ultrasonic time is 1min to 20min; further, the ultrasonic time is 10min.

[0024] Furthermore, the amount of PVDF-HFP particles added is 2g-6g, and the mass fraction is about 10wt% to 30wt%; further, the amount of PVDF-HFP particles added is 3.7466g, and the mass fraction is about 20wt%.

[0025] Further, in S5, the magnetic stirring temperature is 30°C to 90°C;

[0026] Further, in S5, the magnetic stirring temperature is 60°C;

[0027] Further, in S5, the stirring time is 5h to 15h;

[0028] Furthermore, in S5, the stirring time is 10 hours.

[0029] Further, the substrate is a polyvinyl chloride hexagonal mesh screen;

[0030] Furthermore, the scanning starting point is 20mm, the scanning speed is 4mm / s, the scanning stroke is 5mm; the receiving distance is 20cm; the pushing speed is 0.3ml / h; the spinning voltage is -2KV and 22KV; the spinning temperature is about 20-25°C; and the ambient humidity is about 30-40%.

[0031] Furthermore, in S6, the electrospinning time is about 1 hour.

[0032] Furthermore, in S7, the drying temperature is about 80° C. and the drying time is about 4 hours.

[0033] The third purpose of the present invention is to provide an application of a dendritic structure nanofiber air filter material.

[0034] The filtration efficiency η of the dendritic structure nanofiber air filtration material is:

[0035] η=1-C 1 / C0 ;

[0036] Among them, the average value of NaCl aerosol concentration before passing through the material is C 0 , the average NaCl aerosol concentration after passing through the material is C 1 .

[0037] Compared with the prior art, the present invention proposes a dendrite-structured nanofiber air filter material, a preparation method and an application thereof, which have the following beneficial effects:

[0038] 1. The dendrite-structured nanofiber air filter material proposed in the present invention mainly uses polyvinylidene fluoride and hexafluoropropylene as raw materials. The dendrite-structured nanofiber air filter material prepared by electrospinning technology contains more fluorine atoms, which is beneficial to reducing the surface energy of the dendrite-structured nanofiber air filter material, thereby making the dendrite-structured nanofiber air filter material have good hydrophobic properties.

[0039] 2. Application of Ti in the present invention 3 C 2 T x As nanosheets, Ti 3 C 2 T x It has excellent mechanical properties and improves the mechanical properties of dendritic structure nanofiber air filter materials.

[0040] 3. The nanofiber module used in the present invention plays a supporting role, effectively improving the mechanical properties and air permeability of the branch structure nanofiber air filter material; the nanowire module is conducive to reducing the pore size, and is expected to improve the filtration efficiency of the branch structure nanofiber air filter material. BRIEF DESCRIPTION OF THE DRAWINGS

[0041] Figure 1 A scanning electron microscope image of a dendritic nanofiber air filter material of the present invention is shown;

[0042] Figure 2 The optical graphs of mechanical properties of a dendritic nanofiber air filter material of the present invention are shown; wherein (a) is a twisted optical graph of the sample; (b) is a stretched optical graph of the sample; and (c) is a folded optical graph of the sample;

[0043] Figure 3 A scanning electron microscope image of a dendritic nanofiber air filter material of the present invention is shown.

[0044] Figure 4 A scanning electron microscope image of a nanofiber air filter material of a comparative example of the present invention is shown.

[0045] Figure 5A scanning electron microscope image of another nanofiber air filter material of a comparative example of the present invention is shown.

[0046] Figure 6 A scanning electron microscope image of another nanofiber air filter material of a comparative example of the present invention is shown. DETAILED DESCRIPTION

[0047] The exemplary embodiments and comparative examples of the present application will be described in more detail below with reference to the accompanying drawings. Although the exemplary embodiments of the present application are shown in the accompanying drawings, it should be understood that the present application can be implemented in various forms and should not be limited by the embodiments set forth herein. On the contrary, these embodiments are provided in order to enable a more thorough understanding of the present application and to enable the scope of the present application to be fully conveyed to those skilled in the art.

[0048] In the following examples, unless otherwise specified, the technical means adopted are conventional means well known to those skilled in the art, and the reagents and materials in the present invention are obtained from the market or other public channels.

[0049] The experimental materials and equipment involved in the present invention mainly include but are not limited to:

[0050] The molecular weight of N, N-dimethylformamide reagent was 73.09, purity ≥99.9%, and it was purchased from Shanghai Aladdin Biochemical Technology Co., Ltd.;

[0051] The dopamine hydrochloride reagent has a molecular weight of 189.64 and a purity of 98%, and was purchased from Shanghai Aladdin Biochemical Technology Co., Ltd.;

[0052] The weight average molecular weight of the polyvinylidene fluoride co-hexafluoropropylene reagent was 455,000, in granular form, and was purchased from Shanghai MacLean Biochemical Technology Co., Ltd.;

[0053] The polyvinylidene fluoride reagent has a weight average molecular weight of 534,000 and is in granular form and was purchased from Shanghai MacLean Biochemical Technology Co., Ltd.;

[0054] Ti 3 AlC 2 MAX reagent was purchased from Jilin Yiyi Technology Co., Ltd.;

[0055] ZNCL-TS intelligent constant temperature digital display magnetic stirrer was purchased from Shanghai Yushen Instrument Co., Ltd.:

[0056] The TL-Pro electrospinning machine was purchased from Shenzhen Tongli Micro-Nano Technology Co., Ltd.;

[0057] The SX-L1056R1 mask filtration performance test bench was purchased from Suzhou Suxin Environmental Technology Co., Ltd.

[0058] The invention discloses a branch-structured nanofiber air filter material, a preparation method and an application thereof, and the technical principles mainly include: regulating the conductivity of the spinning solution by dopamine hydrochloride and modifying polyvinylidene fluoride-co-hexafluoropropylene by two-dimensional transition metal titanium carbide.

[0059] Based on the above principle, the present invention proposes the following steps:

[0060] S1. Mix 4 g of lithium fluoride with 80 ml of hydrochloric acid in a beaker and stir for 30 min to obtain a hydrofluoric acid solution;

[0061] S2. Titanium carbide aluminum (Ti 3 AlC 2 MAX phase) in the hydrofluoric acid system obtained in step S1, the Al atomic layer is etched away to obtain a two-dimensional titanium carbide (Ti 3 C 2 T x ) nanosheets;

[0062] S3. 0.3 g Ti obtained in step S2 3 C 2 T x Add to 17 ml of solvent and sonicate for 30 min;

[0063] S4. 0.05 g of dopamine hydrochloride was added to the solution obtained in step S3, and then ultrasonicated for 10 min;

[0064] S5. 3.7466 g of PVDF-HFP particles were added to the solution obtained in step S4, and magnetic stirring was performed to obtain an electrospinning solution;

[0065] S6. Lay the substrate flat on the flat receiver of the electrospinning machine, then inject the electrospinning solution obtained in step S5 into the syringe, place the syringe on the electrospinning machine, adjust the parameters for electrospinning, and obtain a bottom layer as the receiving substrate and an upper layer as the branch structure nanofiber air filter material;

[0066] S7. Place the nanofiber membrane obtained in step S6 in a stainless steel sterilization tray, and then place the stainless steel sterilization tray in a vacuum drying oven to dry for a certain period of time to obtain a dendritic structure nanofiber air filtration material.

[0067] The material of the present invention mainly includes polyvinylidene fluoride co-hexafluoropropylene, polyvinylidene fluoride, two-dimensional transition metal titanium carbide Ti 3 C 2 T x, dopamine hydrochloride, etc., by modifying the raw material polyvinylidene fluoride co-hexafluoropropylene with two-dimensional transition metal titanium carbide, and using dopamine hydrochloride to regulate the conductivity of the spinning solution. The dendritic structure nanofiber air filter material of the present invention effectively improves the mechanical properties of the fiber and the stability of the spinning solution in the electric field, has good mechanical properties, hydrophobicity and reusability, and is effective in ultrafine particles such as PM 0.3 The filtration efficiency can reach over 99.96%, and it has great application potential in the fields of air filtration and medical health.

[0068] Example 1

[0069] The invention provides a preparation method for a dendritic structure nanofiber air filter material with an addition amount of 0.05 g of dopamine hydrochloride.

[0070] Mainly include:

[0071] The two-dimensional titanium carbide Ti used in this example 3 C 2 T x The nanosheets were prepared by hydrofluoric acid etching.

[0072] First, use a 10 ml measuring cylinder to weigh 17 ml of N, N-dimethylformamide (DMF) solvent twice and pour it into a 25 ml beaker. The weight of DMF solvent is 14.9062 g. Next, use a balance to weigh 0.03 g of Ti 3 C 2 T x The nanopowder was added into a beaker containing DMF. 3 C 2 T x The nanopowder is dispersed in the solvent in a uniform size, and the beaker is placed in an ultrasonic cleaner for 30 minutes. Then, 0.05g of dopamine hydrochloride powder is weighed on a balance and added to the above 25ml beaker, and the above solution is placed in an ultrasonic cleaner for 10 minutes. After the ultrasound is completed, 3.7466g of PVDF-HFP particles are weighed and added to the above 25ml beaker, and after adding a magnetic stirrer to the beaker, the beaker is placed in a temperature-controlled magnetic stirrer, and stirred at 1800rpm for 10 hours at 60°C to obtain a black viscous spinning solution with a PVDF-HFP mass fraction of about 20wt%.

[0073] 7ml of spinning solution was placed in a 10ml syringe, and a 19G spinning needle was installed on the syringe. The syringe was placed in a TL-Pro electrospinning machine, and a 15cm×20cm 316 stainless steel plate was used as a receiver. The scanning starting point was 20mm, the scanning speed was 4mm / s, the scanning stroke was 5mm, the receiving distance was 20cm, the pushing speed was 0.3ml / h, the receiving substrate was a polyvinyl chloride hexagonal mesh screen, the spinning voltage was -2KV and 22KV, the spinning temperature was about 20-25℃, the humidity was about 35-40%, and the spinning time was about 1h. Then, the prepared nanofiber membrane was placed in a stainless steel sterilization tray, and then the stainless steel sterilization tray was placed in a vacuum drying oven at 80℃ for 4h to obtain a dendritic nanofiber air filtration material.

[0074] Results: See Figure 1 The nanofiber membrane is about 12 cm long and 8 cm wide. The fiber membrane is composed of disorderly distributed 100-200 nm fibers as the main framework. The coarse fibers are connected by 40-90 nm nanowires. The fiber membrane has good resistance to PM 0.3 The filtration efficiency is as high as 99.97%. Figure 2 (a), 2(b) and 2(c), the nanofiber membrane can be folded, bent and stretched, showing good mechanical properties.

[0075] Example 2

[0076] The invention provides a preparation method for a dendritic structure nanofiber air filter material with an addition amount of 0.15 g of dopamine hydrochloride.

[0077] Mainly include:

[0078] The two-dimensional titanium carbide Ti used in this example 3 C 2 T x The nanosheets were prepared by hydrofluoric acid etching.

[0079] First, use a 10 ml measuring cylinder to weigh 17 ml of N, N-dimethylformamide (DMF) solvent twice and pour it into a 25 ml beaker. The weight of DMF solvent is 14.9062 g. Next, use a balance to weigh 0.03 g of Ti 3 C 2 T x The nanopowder was added into a beaker containing DMF. 3 C 2 T xThe nanopowder is dispersed in the solvent in a uniform size, and the beaker is placed in an ultrasonic cleaner for 30 minutes. Then, 0.15g of dopamine hydrochloride powder is weighed on a balance and added to the above 25ml beaker, and the above solution is placed in an ultrasonic cleaner and continues to be ultrasonicated for 10 minutes. After the ultrasound is completed, 3.75g of PVDF particles are weighed and added to the above 25ml beaker, and after adding a magnetic stirrer to the beaker, the beaker is placed in a temperature-controlled magnetic stirrer, and stirred at 1800rpm for 10 hours at 60°C to obtain a black viscous spinning solution with a PVDF mass fraction of about 20wt%.

[0080] 5ml spinning solution was placed in a 10ml syringe, and a 19G spinning needle was installed on the syringe. The syringe was placed in a TL-Pro electrospinning machine, and a 15cm×20cm 316 stainless steel plate was used as a receiver. The scanning starting point was 20mm, the scanning speed was 4mm / s, the scanning stroke was 5mm, the receiving distance was 20cm, the pushing speed was 0.3ml / h, the receiving substrate was a polyvinyl chloride hexagonal mesh screen, the spinning voltage was -2KV and 22KV, the spinning temperature was about 20-25℃, the humidity was about 35-40%, and the spinning time was about 1h. Then, the prepared nanofiber membrane was placed in a stainless steel sterilization tray, and then the stainless steel sterilization tray was placed in a vacuum drying oven at 80℃ for 4h to obtain a dendritic structure nanofiber air filtration material.

[0081] Results: See Figure 3 The nanofiber membrane is microscopically composed of disorderly distributed 150-250nm fibers as the main framework, and the coarse fibers are connected to each other by 50-100nm nanowires, presenting a typical tree branch structure.

[0082] Comparative Example 1

[0083] The invention provides a preparation method for a nanofiber air filter material with zero dopamine hydrochloride content.

[0084] Mainly include:

[0085] The two-dimensional titanium carbide Ti used in this example 3 C 2 T x The nanosheets were prepared by hydrofluoric acid etching.

[0086] First, use a 10 ml graduated cylinder to weigh 17 ml of N,N-dimethylformamide (DMF) solvent twice and pour it into a 25 ml beaker. The weight of DMF solvent is 14.9062 g. Next, use a balance to weigh 0.03 g of Ti 3 C 2 T xThe nanopowder was added into a beaker containing DMF. 3 C 2 T x The nanopowder is dispersed in the solvent in a uniform size. The beaker is placed in an ultrasonic cleaner for 30 minutes. After the ultrasonic treatment, 3.7466 g of PVDF-HFP particles are weighed and added to the above 25 ml beaker. After adding a magnetic stirrer to the beaker, the beaker is placed in a temperature-controlled magnetic stirrer and stirred at 1800 rpm for 10 hours at 60 ° C to obtain a black viscous spinning solution with a PVDF-HFP mass fraction of about 20 wt%.

[0087] 4ml spinning solution was placed in a 10ml syringe, and a 19G spinning needle was installed on the syringe. The syringe was placed in a TL-Pro electrospinning machine, and a 15cm×20cm 316 stainless steel plate was used as a receiver. The scanning starting point was 20mm, the scanning speed was 4mm / s, the scanning stroke was 5mm, the receiving distance was 20cm, the pushing speed was 0.3ml / h, the receiving substrate was a polyvinyl chloride hexagonal mesh screen, the spinning voltage was -2KV and 22KV, the spinning temperature was about 20-25℃, the humidity was about 35-40%, and the spinning time was about 1h. Then, the prepared nanofiber membrane was placed in a stainless steel sterilization tray, and then the stainless steel sterilization tray was placed in a vacuum drying oven at 80℃ for 4h to obtain a nanofiber air filter material.

[0088] Results: See Figure 4 The fiber diameter of the nanofiber membrane is in the range of 50 to 150 nm, the fiber diameter is uneven, and there is no obvious tree structure.

[0089] Comparative Example 2

[0090] The invention provides a preparation method for a nanofiber air filter material with an addition amount of 0.15 g of dopamine hydrochloride.

[0091] Mainly include:

[0092] The two-dimensional titanium carbide Ti used in this example 3 C 2 T x The nanosheets were prepared by hydrofluoric acid etching.

[0093] First, use a 10 ml measuring cylinder to weigh 17 ml of N, N-dimethylformamide (DMF) solvent twice and pour it into a 25 ml beaker. The weight of DMF solvent is 14.9062 g. Next, use a balance to weigh 0.03 g of Ti 3 C 2 T xThe nanopowder was added into a beaker containing DMF. 3 C 2 T x The nanopowder is dispersed in the solvent in a uniform size, and the beaker is placed in an ultrasonic cleaner for 30 minutes. Then, 0.15g of dopamine hydrochloride powder is weighed on a balance and added to the above 25ml beaker, and the above solution is placed in an ultrasonic cleaner for 10 minutes. After the ultrasound is completed, 3.7466g of PVDF-HFP particles are weighed and added to the above 25ml beaker, and after adding a magnetic stirrer to the beaker, the beaker is placed in a temperature-controlled magnetic stirrer, and stirred at 1800rpm for 10 hours at 60°C to obtain a black viscous spinning solution with a PVDF-HFP mass fraction of about 20wt%.

[0094] 6ml spinning solution was placed in a 10ml syringe, a 19G spinning needle was installed on the syringe, and the syringe was placed in a TL-Pro electrospinning machine, and a 15cm×20cm 316 stainless steel plate was used as a receiver. The scanning starting point was 20mm, the scanning speed was 4mm / s, the scanning stroke was 5mm, the receiving distance was 20cm, the pushing speed was 0.3ml / h, the receiving substrate was a polyvinyl chloride hexagonal mesh screen, the spinning voltage was -2KV and 22KV, the spinning temperature was about 20-25℃, the humidity was about 35-40%, and the spinning time was about 1h. Then, the prepared nanofiber membrane was placed in a stainless steel sterilization tray, and then the stainless steel sterilization tray was placed in a vacuum drying oven at 80℃ for 4h to obtain a dendritic nanofiber air filtration material.

[0095] Results: See Figure 5 The fiber diameter of the nanofiber membrane is in the range of 70 to 120 nm, the fiber diameter is uniform, and there are a large number of protrusions on the fiber surface, but there is no obvious tree structure.

[0096] Comparative Example 3

[0097] The invention provides a preparation method for a nanofiber air filter material with an addition amount of 0.25 g of dopamine hydrochloride.

[0098] Mainly include:

[0099] The two-dimensional titanium carbide Ti used in this example 3 C 2 T x The nanosheets were prepared by hydrofluoric acid etching.

[0100] First, use a 10 ml measuring cylinder to weigh 17 ml of N, N-dimethylformamide (DMF) solvent twice and pour it into a 25 ml beaker. The weight of DMF solvent is 14.9062 g. Next, use a balance to weigh 0.03 g of Ti 3 C 2 T x The nanopowder was added into a beaker containing DMF. 3 C 2 T x The nanopowder is dispersed in the solvent in a uniform size, and the beaker is placed in an ultrasonic cleaner for 30 minutes. Then, 0.25g of dopamine hydrochloride powder is weighed on a balance and added to the above 25ml beaker, and the above solution is placed in an ultrasonic cleaner for 10 minutes. After the ultrasound is completed, 3.7466g of PVDF-HFP particles are weighed and added to the above 25ml beaker, and after adding a magnetic stirrer to the beaker, the beaker is placed in a temperature-controlled magnetic stirrer, and stirred at 1800rpm for 10 hours at 60°C to obtain a black viscous spinning solution with a PVDF-HFP mass fraction of about 20wt%.

[0101] 6ml spinning solution was placed in a 10ml syringe, a 19G spinning needle was installed on the syringe, and the syringe was placed in a TL-Pro electrospinning machine, and a 15cm×20cm 316 stainless steel plate was used as a receiver. The scanning starting point was 20mm, the scanning speed was 4mm / s, the scanning stroke was 5mm, the receiving distance was 20cm, the pushing speed was 0.3ml / h, the receiving substrate was a polyvinyl chloride hexagonal mesh screen, the spinning voltage was -2KV and 22KV, the spinning temperature was about 20-25℃, the humidity was about 35-40%, and the spinning time was about 1h. Then, the prepared nanofiber membrane was placed in a stainless steel sterilization tray, and then the stainless steel sterilization tray was placed in a vacuum drying oven at 80℃ for 4h to obtain a dendritic nanofiber air filtration material.

[0102] Results: See Figure 6 The fiber diameter of the nanofiber membrane is in the range of 60 to 110 nm, the fiber diameter is mainly thin, and there is no obvious tree structure.

[0103] The filtration performance test reference standards of the nanofiber air filter material in the present invention mainly include:

[0104] GB / T32610-2016 Technical Specifications for Daily Protective Masks, GB2026-2006 Respiratory Protective Equipment - Self-priming Filter-type Particulate Respirator, GB19082-2009 Technical Requirements for Medical Disposable Protective Clothing, GB19083-2010 Technical Requirements for Medical Protective Masks, etc.

[0105] According to the above method, the filtration performance of the dendritic nanofiber air filter material of Example 1 of the present invention and the nanofiber air filter materials prepared in Comparative Examples 2 and 3 were tested.

[0106] Results: Please refer to Table 1. The dendritic structure nanofiber air filter material prepared in Example 1 has an effect on the salt particles PM 0.3 、PM 0.5 and PM 1 The filtration efficiencies of the nanofiber air filtration materials prepared in Comparative Examples 2 and 3 were 99.97%, 99.997% and 100% respectively, showing excellent ultrafine particle filtration efficiency, which is mainly due to the physical interception effect of the dendrite structure on ultrafine particles. 0.3 、PM 0.5 and PM 1 The filtration efficiency is also close to that of the tree-structured nanofiber air filter material. This is mainly because the fiber diameter is small, which makes the fiber membrane pores small, but it is easy to cause higher air resistance.

[0107] Table 1 Filtration efficiency of dendritic nanofiber air filter materials

[0108]

[0109] It should be noted that the term "comprises" or any other variation thereof is intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only these elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device. In the absence of further restrictions, the elements defined by the sentence "comprises..." do not exclude the existence of other identical elements in the process, method, article or device including the elements.

[0110] The above are only embodiments of the present application and are not intended to limit the present application. For those skilled in the art, the present application may have various changes and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present application should be included within the scope of the claims of the present application.

Claims

1. A dendritic nanofiber air filter material, characterized in that: The dendritic structure nanofiber air filter material comprises a frame module and a filter module; The frame module is Ti3C2T x Functionalized polyvinylidene fluoride-co-hexafluoropropylene nanofiber membrane; The filter module is Ti3C2T x Functionalized polyvinylidene fluoride-co-hexafluoropropylene nanowires.

2. The dendritic structure nanofiber air filter material according to claim 1, characterized in that: The Ti3C2T x Functionalized polyvinylidene fluoride-co-hexafluoropropylene nanofiber membrane is a disordered distribution of nanofibers; The Ti3C2T x Functionalized polyvinylidene fluoride co-hexafluoropropylene nanowires are interconnected, showing a typical tree structure.

3. The dendritic structure nanofiber air filter material according to claim 1, characterized in that: The fiber diameter of the framework module is about 100nm to 200nm; The diameter of the filter module nanowire is about 20nm to 80nm.

4. A method for preparing a dendritic nanofiber air filter material, characterized in that: The method for applying the dendritic nanofiber air filter material according to any one of claims 1 to 3 comprises: S1. Mixing lithium fluoride and hydrochloric acid, stirring magnetically, to obtain a hydrofluoric acid solution; S2. Etching away the Al atomic layer of titanium carbide in the hydrofluoric acid solution to obtain a two-dimensional titanium carbide nanosheet Ti3C2T x ; S3. The two-dimensional titanium carbide nanosheet Ti3C2T x , added to N, N-dimethylformamide solution, and ultrasonically vibrated to obtain a solution in which two-dimensional titanium carbide nanosheets are dispersed in N, N-dimethylformamide in uniform size; S4. adding dopamine hydrochloride to a solution of the two-dimensional titanium carbide nanosheets dispersed in N,N-dimethylformamide in uniform size, and ultrasonically vibrating to obtain a two-dimensional titanium carbide nanosheet solution having good electrical conductivity; S5. adding PVDF-HFP to the two-dimensional titanium carbide nanosheet solution having good electrical conductivity, and magnetically stirring to obtain an electrospinning solution; S6. Laying the substrate flat on a flat receiver of an electrospinning machine, injecting the electrospinning solution into a syringe, placing the syringe on the electrospinning machine, adjusting parameters for electrospinning, controlling the spinning time, and preparing nanofiber membranes of different thicknesses; S7. Place the nanofiber membrane in a stainless steel sterilization tray, place the stainless steel sterilization tray in a vacuum drying oven, and dry for a certain period of time to completely evaporate the solvent to obtain a dendritic structure nanofiber air filtration material.

5. The preparation method according to claim 4, characterized in that: The hydrochloric acid concentration is 6 mol / L to 12 mol / L; The lithium fluoride accounts for 10% to 20% of the hydrochloric acid; In S1, the stirring time is 10 min to 2 h.

6. The preparation method according to claim 4, characterized in that: The titanium aluminum carbide is Ti3AlC2 MAX phase; The two-dimensional titanium carbide nanosheet is Ti3C2T x ; Wherein, x is a number, which is a natural number; T is a surface terminal group; and the surface terminal group includes -F, -Cl, -OH or =O.

7. The preparation method according to claim 4, characterized in that: The Ti3C2T x The mass ratio of the N,N-dimethylformamide solvent is 1:300 to 1:700; The Ti3C2T x The mass is 0.01g-0.05g, and the volume of the N,N-dimethylformamide is 10ml-24ml; In S3, the ultrasonic time is 10 minutes to 2 hours.

8. The preparation method according to claim 4, characterized in that: The amount of dopamine hydrochloride added is 0 to 0.25 g; In S4, the ultrasonic time is 1 min to 20 min.

9. The preparation method according to claim 4, characterized in that: The PVDF-HFP particles are added in an amount of 2g-6g, with a mass fraction of about 10wt% to 30wt%; In S5, the magnetic stirring temperature is 30°C to 90°C; In S5, the stirring time is 5h to 15h; In S6, the substrate is a polyvinyl chloride hexagonal mesh screen; In S6, the electrospinning time is about 0.5h to 2.0h.

10. An application of the air filter material obtained by the dendritic nanofiber air filter material according to any one of claims 1 to 3 or the preparation method according to any one of claims 4 to 9, characterized in that: The filtration efficiency η of the dendritic structure nanofiber air filtration material is: η=1-C1 / C0; Among them, the average value of NaCl aerosol concentration before passing through the material is C0, and the average value of NaCl aerosol concentration after passing through the material is C1.